Estratégias para melhorar o fornecimento de nitrogênio ao milho e ao trigo por dejetos suínos e reduzir a emissão de óxido nitroso do solo - Schirmann, Janquieli (2012)
The swine manure is a major source of nitrogen (N) to crops, although its inappropriate use can lead to N losses which in return pollute environment and reduces its value as organic fertilizer. The sustainability of pig farming depends on strategies that could improve crops N utilization from pig slurry and mitigate harmful environmental impact caused by its use. The objective of this study was to evaluate the effect of full and split pig slurry (PS) application in no-till corn and wheat, with and without nitrification inhibitor (NI), on: N accumulation, productivity, and nitrous oxide (N2O) emissions. The study was conducted from November 2010 to November 2011 on a typic Hapludalf. The treatments used in corn and wheat were: 1) control; 2) PS full (pre-planting); 3) PS split (1/3 at pre-planting and 2/3 sidedressing); 4) PS full + NI; 5) PS split + IN; 6) mineral NPK. Agrotain Plus was used as NI as it contains 81 % of dicyandiamide (DCD). It was used at a rate of 7 kg ha-1. The use of PS increased N accumulation and yield of maize/wheat crops and were at par with NPK mineral fertilizer. However, N2O emission was increased with PS and NPK application. Split application of PS and NI did not affected N accumulation and yield of maize and wheat crops however splitting of PS reduced N2O emissions from wheat crop. The use of NI reduced N2O soil emissions in both crops and in the two methods of PS application. On an average, N2O emission was reduced by 15.5% and 45.0 % in maize and wheat, respectively. From the results it was apparent that, the strategy of combining NI with PS could reduce environmental implications associated with the sole use of PS.